Impact of learning organization, quality of work life, networking, mentoring, self-efficacy, and career advancement among academics in two universities in Hamadan, Iran - Parsa, Bita (2014)
Despite the importance of learning organization and social organizational factors in career advancement and promotion among academic employees,still there are academic employees who suffer from low career advancement and consequently low academic performance. The results of studies in this area did not provide enough attention to factors contributing to career advancement. In addition, not much effort has been done to examine the impact of relationship between learning organization, quality of work life, networking, mentoring and self- efficacy with career advancement. Therefore, this study aims to develop a comprehensive model for career advancement through mediating effect of self- efficacy among academic employees in the two public universities in Hamadan, Iran namely,Hamadan University of Medical Sciences (HUMS) and Bu_Ali Sina University (BASU). This survey research was done among 307 academics employees in two universities (162 in HUMS and 145 in BASU) to determine predictors of their career advancement. Participants were identified by probability proportional to size sampling. Self-administered questionnaires were used to collect data. The Structural Equation Modeling (SEM) methodology was applied to determine the best fitted model to predict career advancement. This model was able to explain how independent (exogenous) variables such as quality of work life, learning organization, mentoring and networking lead to career advancement (endogenous) and how self-efficacy mediates the relationship between exogenous variables and career advancement. The fit indices reveal an acceptable fit for model. Testing of research hypotheses was performed using the Pearson’s correlation analysis and SEM. The results show that learning organization,quality of work life, mentoring, networking and self efficacy were related to academic career advancement (p<0.05). The total effect (ß) of learning organization, mentoring, network, organization support, and quality of work life on career advancement was .381, .174, .355 and .288 respectively. The findings show self-efficacy has partially mediated the relationship between career advancement with learning organization, mentoring and networking. Therefore, universities may strength their academic self- efficacy as an alternative to increase career advancement. As shown learning organization and networking behaviour had highest impact on career advancement. Thus, universities may focus more on enhancing continuous learning, improve interpersonal relationship to enable academic staff to exchange knowledge and skills in conducting appropriate mentoring programs. The nature of self-efficacy as a mediator implied that career advancement of academic employees can be improve if these persons believe their self abilities in their workplace. Academics need to be equipped with appropriate skills such as learning organization characteristics,mentoring and networking to increase academics’ self-efficacy and career advancement.